Perianal and gluteal parasitic abscess of Enterobius vermicularis: case report and review of the literature - Akyel, Nazlı Gülsüm; Banaz, Tuba; Arı Gökhan, Burcu (The Turkish Journal of Pediatrics, 2026)
Background. Enterobius vermicularis is a nematode that predominantly affects the pediatric population, particularly in families with school-aged children. While it typically causes intestinal symptoms, rare cases of extraintestinal involvement have been reported, including female genital tract involvement and complications such as appendicitis or enterocolitis. Perianal parasitic abscesses are also rare, with only a few cases reported in the literature. Case Presentation. A 17-year-old female presented with abdominal pain during menstruation. Pelvic ultrasound revealed a septated cystic lesion located posterior to the uterus. Magnetic resonance imaging (MRI) demonstrated a perianal lesion with thick material, appearing iso- to hyperintense on both T1- and T2-weighted images. The lesion extended into the left gluteal muscles and showed peripheral contrast enhancement and diffusion restriction. Notably, there were no surrounding inflammatory changes, making an abscess diagnosis less likely. Surgical drainage revealed pus, and cytological analysis identified abundant parasitic oocytes consistent with E. vermicularis. The patient was treated with surgical drainage followed by pyrantel pamoate, resulting in near-complete resolution of the lesion at the one-month follow-up MRI. A literature review was also conducted to identify previously reported cases of parasitic abscesses and to explore the differential diagnoses of perianal cystic lesions. Conclusions. Perianal abscesses due to parasitic infections are rare, particularly those caused solely by E. vermicularis. Given the high prevalence in childhood infestations, parasitic abscesses should be considered in the differential diagnosis of perianal collections in pediatric patients, especially in the absence of peripheral inflammatory signs.